A health political science for health promotion. (December 2021) - de Leeuw, Evelyne; Harris, Patrick; Kim, Jinhee; Yashadhana, Aryati
If health promotion as a field of change for human and ecological health is to maintain its urgency, it needs to continue building its policy credentials. This paper charts the development of policy as a concern for IUHE/IUHPE (International Union for Health Education/International Union for Health Promotion and Education) from the mid-1970s when 'health education policies' were prominent issues, to the launch of Healthy Public Policy (in the 1980s) and Health in All Policy (in the 2000s). We argue that solid conceptual and theoretical foundations exist to frame and develop the relevance and connectedness of health promotion more prominently. We start off with a brief introduction into (health) political science, and then illustrate the urgency of the argument with three case studies. The first takes a critical realist perspective on 'closing the gap' in Australian Indigenous populations. With recent evidence it demonstrates that the core of the policymaking process needs to re-align itself with an Indigenous narrative. The second case study reviews the politics of healthy urban planning and health equity in cities. Taking a critical theory institutionalist view, the case describes how the political and narrative parallels between urban theory and health equity have gone underexplored. With an explicit gaze to connect the two, the field could become a large and influential driver of enhanced health promotion and public health policy. The third case describes the languages, policy frames, and distinctions, in four urban/health paradigms. It shows that unconscious policy and practice bias exists in policy priorities and processes. We conclude with observations and recommendations on the role of health promotion as a conceptual realm and field of activity. We show that all health promoters should be aware of the political nature of their enterprise. Tools and analyses exist to help further action.